Uji Patogenisitas Fungi Entomopatogen Lokal Riau sebagai Agen Biokontrol Hama Rayap (Coptotermes curvignathus Holmgren) - SINTAWATI, REGIANA; MARTINA, ATRIA; LINDA, TETTY MARTA (Jurusan Biologi FMIPA Universitas Riau, 2016)
Biopesticide is a technique that can be used to the control pest population in the environment. Thepurpose of this research was to isolate fungi from the soil using baiting and cadaver technique andpathogenicity test. Isolates which had high germinating conidia was tested their patogenicity againstCoptotermes curvignathus. A total of 12 isolates were baited from soil and cadaver samples at palm oilplantation. The result showed eight isolates had high germinating conidia categories (Ë 80%). Thepathogenicity test of four isolates showed 100% mortality for RB.r01 and BK.r01; and KB.r01 andNK.r01were 72% and 67% respectively. Isolates capability against termite was not significantly different,but it was significantly different from control.Keywords : entomopathogenic fungi, pathogenicity, Coptotermes curvignathus, biocontrol